2019
DOI: 10.3390/molecules24030644
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Potential Gallium-68-Labelled Radiotracer Based on DOTA-Curcumin for Colon-Rectal Carcinoma: From Synthesis to In Vivo Studies

Abstract: Colorectal cancer is the third most commonly occurring cancer in men and the second most commonly occurring cancer in women worldwide. We have recently reported that curcuminoid complexes labelled with gallium-68 have demonstrated preferential uptake in HT29 colorectal cancer and K562 lymphoma cell lines compared to normal human lymphocytes. In the present study, we report a new gallium-68-labelled curcumin derivative (68Ga-DOTA-C21) and its initial validation as marker for early detection of colorectal cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…It was found that the Mn 2+ -curcumin complex is stable in physiological buffers and media, as opposed to curcumin, even under reducing conditions [32]. The gallium complexed curcumin increases the stability, cellular uptake, and bioavailability of curcumin in both in vitro and in vivo cancer models [110]. In a study, a gallium-curcumin complex and gallium-diacetylcurcumin showed a higher uptake by colorectal carcinoma (HT29) and lymphoma (K562) cell lines than in lymphocytes [111].…”
Section: Solubility Stability and Cellular Uptake Of Metal-curcumin Complexesmentioning
confidence: 99%
“…It was found that the Mn 2+ -curcumin complex is stable in physiological buffers and media, as opposed to curcumin, even under reducing conditions [32]. The gallium complexed curcumin increases the stability, cellular uptake, and bioavailability of curcumin in both in vitro and in vivo cancer models [110]. In a study, a gallium-curcumin complex and gallium-diacetylcurcumin showed a higher uptake by colorectal carcinoma (HT29) and lymphoma (K562) cell lines than in lymphocytes [111].…”
Section: Solubility Stability and Cellular Uptake Of Metal-curcumin Complexesmentioning
confidence: 99%
“…Based on these findings, a new series of compounds in which gallium-68 was stably coordinated by several bifunctional chelators (namely, DOTA, NODAGA and AAZTA) tethered to a curcumin-based molecular vector was developed [ 51 , 73 ]. Synthesis of these derivatives generally entailed a first step in which the curcuminoid was functionalised with a protected spacer able to bind the chelator upon cleavage of the protecting group.…”
Section: Curcumin Derivatives Labelled With Metal Radionuclidesmentioning
confidence: 99%
“… In vivo PET images at 65 min of [ 18 F]FEE-PCur ( A ) and [ 18 F]FEEM-PCur ( B ) in C6 glioma-bearing mice, and at 60 min of [ 68 Ga]Ga-DOTA-C21 in a HT29 colorectal tumour-bearing mouse ( C ). Figure has been obtained by merging and elaborating images from references [ 50 , 51 ]. Reprinted with permission from [ 50 , 51 ].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Exploiting the promising tumor-targeting ability of curcumin and its derivatives, Orteca and her group synthesized a new 68 Ga-labeled curcumin derivative for PET imaging of colorectal cancer [31]. Indeed, in previous studies [115,116], the authors synthesized and characterized 68 Ga-labeled complexes with curcumin, diacetyl-curcumin, and bis(dehydroxy)curcumin, but these compounds underwent rapid degradation in whole human blood.…”
Section: Conjugates For Pet Imagingmentioning
confidence: 99%